DETERMINING LEGAL STATUS AND LIABILITY OF AUTONOMOUS ARTIFICIAL INTELLIGENCE SYSTEM IN ISLAMIC SMART CONTRACTS - Ahmad Saparwadi; FX Joko Priyono; Ro'fah Setyowati (Fakultas Hukum, Universitas Diponegoro, 2026)
The rapid development of artificial intelligence has given rise to autonomous systems capable of performing acts with legal consequences, particularly through smart contracts. This development presents a fundamental challenge to Islamic contract law: whether autonomous AI can possess the legal capacity required to become a contracting party and how liability arising from its acts should be determined. To address these questions, this study employs doctrinal legal research using philosophical and conceptual approaches. Primary, secondary, and tertiary legal materials were collected through documentary research and examined using argumentative legal analysis. The findings demonstrate that autonomous AI does not satisfy the requirement of al-‘āqil, namely a rational legal subject possessing full ahliyyah al-adā’ or legal capacity to perform legally valid acts, as attributed to human beings. Nevertheless, this study advances a novel argument based on qiyās al-adnā by analogizing the operational status of autonomous AI to the classical legal position of an authorized slave, or ‘abd ma’dhūn, who acts with the permission of his master. On this basis, autonomous AI may be understood not as an independent legal person, but as a non-human instrument operating within a delegated authority. Consequently, the validity of smart contracts may be recognized through the concept of wakālah muqayyadah, while liability for the AI’s acts is attributed to the principal or muwakkil. In cases involving multiple parties, this study further proposes the integration of kafālah and takāful as mechanisms for allocating and collectively managing liability.